Acute S100B in serum is associated with cognitive symptoms and memory performance 4 months after paediatric mild traumatic brain injury. (6th December 2015) - Studer, Martina; Goeggel Simonetti, Barbara; Heinks, Theda; Steinlin, Maja; Leichtle, Alexander; Berger, Steffen; Joeris, Alexander
Abstract: Objective : This study explored whether acute serum marker S100B is related with post-concussive symptoms (PCS) and neuropsychological performance 4 months after paediatric mild traumatic brain injury (mTBI). Research design and methods : This prospective short-term longitudinal study investigated children (aged 6–16 years) with mTBI ( n = 36, 16 males) and children with orthopaedic injuries (OI, n = 27, 18 males) as a control group. S100B in serum was measured during the acute phase and was correlated with parent-rated PCS and neuropsychological performance 4 months after the injury. Main outcomes and results : The results revealed no between-group difference regarding acute S100B serum concentration. In children after mTBI, group-specific significant Spearman correlations were found between S100B and post-acute cognitive PCS ( r = 0.54, p = 0.001) as well as S100B and verbal memory performance ( r = −0.47, p = 0.006). In children after OI, there were insignificant positive relations between S100B and post-acute somatic PCS. In addition, insignificant positive correlations were found between neuropsychological outcome and S100B in children after OI. Conclusions : S100B was not specific for mild brain injuries and may also be elevated after OI. The group-specific association between S100B and ongoing cognitive PCS in children after mTBI should motivate to examine further the role of S100B as a diagnostic biomarker in paediatric mTBI.